2004
DOI: 10.1103/physrevlett.93.073902
|View full text |Cite
|
Sign up to set email alerts
|

Negative Refraction at Infrared Wavelengths in a Two-Dimensional Photonic Crystal

Abstract: We report on the first experimental evidence of negative refraction at telecommunication wavelengths by a two-dimensional photonic crystal field. Samples were fabricated by chemically assisted ion beam etching in the InP-based low-index constrast system. Experiments of beam imaging and light collection show light focusing by the photonic crystal field. Finite-difference time-domain simulations confirm that the observed focusing is due to negative refraction in the photonic crystal area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
167
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(169 citation statements)
references
References 16 publications
2
167
0
Order By: Relevance
“…The negative refraction effect in photonic crystals at the frequencies close to the band-gap edges was reported by Notomi in [13,14] and the sub-wavelength imaging using flat lenses formed by photonic crystals was demonstrated both theoretically [15,16,17,18,19] and experimentally [20,21]. Unfortunately, the resolution of such lenses is strictly limited by period of the crystal.…”
mentioning
confidence: 99%
“…The negative refraction effect in photonic crystals at the frequencies close to the band-gap edges was reported by Notomi in [13,14] and the sub-wavelength imaging using flat lenses formed by photonic crystals was demonstrated both theoretically [15,16,17,18,19] and experimentally [20,21]. Unfortunately, the resolution of such lenses is strictly limited by period of the crystal.…”
mentioning
confidence: 99%
“…Phys. 118, 075103 (2015) features of the ultrafast modulated heat conduction in very thin layers, as discussed by Berrier et al, 38 and the references therein. Table I.…”
Section: -12mentioning
confidence: 63%
“…But at the optical region, it seems very difficult to make such metallic structures. However, in optical region, it has been shown that two-dimensional photonic crystals (2D PC) can act as effective media with a negative effective refractive index in some frequency regions if being properly designed [7][8][9][10][11][12][13]. Luo et al [8] have studied all-angle negative refraction (AANR) effect in 2D PC that does not employ a negative effective index of refraction.…”
Section: Introductionmentioning
confidence: 99%